Implementasi Metode Talaqqi Dalam Pembelajaran Tahfidzul Qur’an - M. Zainuddin Alanshari; Hepi Ikmal; Moch Faizin Muflich; Siti Uswatun Khasanah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This research is entitled Implementation of talaqqi Method in Tahfidzul Qur’an Learning for student class VIII MTs Terpadu Roudlotul Qur’an Lamongan by using qualitative research, descriptive research, and descriptive approach. The purpose of this study was to determine the planning of the talaqqi method in learning tahfidzul Quran, knowing the implementation of the talaqqi method in learning tahfidzul Quran, and knowing the evaluation of the talaqqi method in learning tahfidzul Quran Student class VIII at MTs Terpadu Roudlotul Quran Lamongan. The first result of this research is the planning of the talaqqi method in learning Tahfidzul Qur’an which is shown through: preparation of activity program plans using a syllabus that is more mapped to competency standards and basic competencies so that it can achieve the predetermined target, namely memorizing chapters 30 and 29 (important letter). The second result of this research is the implementation of the talaqqi method in learning Tahfidzul Qur’an which is shown through preliminary activities starting from the habit of praying before and after starting the lesson. The core activity is carried out by depositing memorization in turn to the tahfidz teacher, the implementation is carried out 2 times a week with 2 hours of lessons, namely Tuesday and Friday. The third result of this research is the evaluation of learning is carried out in two stages, namely test and non-test. For the evaluation of the test, it is done by giving questions to students so that students also understand the writing of their memorization and for non-test evaluation, it is done by checking the student’s BSS books by the teacher at MTs Terpadu Roudlotul Quran Lamongan.